146. Intact Sense of Taste and Smell During COVID-19 Infection Is Associated with Absence of of SARS-CoV-2 Spike Protein Antibody Responses within 3 Months of Symptomatic Illness. (4th December 2021) - Wilson, James M; Gillani, Sheena; Bencshop, Robert; Poorbaugh, Josh; Nirula, Ajay; Zhang, Lin; Keckler, Kody; Weber, Kathleen; Morack, Ralph; Beasley, Stephanie; Brothers, Jennifer; Huhn, Gregory
Abstract: Background: Although studies show most COVID-19 survivors have post-infection immunity against SARS-CoV-2 that could prevent re-infection, there is still a need to identify the breadth of antibody (Ab) responses associated with clinical phenotypes. We characterized Ab profiles at the estimated peak of Ab diversity among adults with recovered SARS-CoV-2 infections and determined their relationships with clinical factors. Methods: From April-June 2020, 41 health system employees with PCR-confirmed symptomatic COVID-19 infection enrolled 8-10 weeks after symptom onset. Symptom questionnaires including baseline demographics, COVID-19 symptoms, disease severity, and disease duration were collected and plasma samples were assayed using a custom Luminex Multiplex platform (Figure 1) to measure the antibody response against 20 COVID-19 related antigens (Figure 2). Differences in Ab profile titers among different groups were tested using nonparametric t test and Benjamini-Hochberg adjustment for multiplicity. Associations were considered significant at FDR< 0.05. Figure 1: Description of the Luminex Serology Assay Figure 2: List of the COVID-19 Related Antigens and Controls Measured Results: Mean age was 48 years (range 27-68), with 51% female, 37% White, 32% Black, 29% Asian, and 17% LatinX. Ab profiles (Figure 3) showed 100% cross-reactivity with related alpha and beta coronavirus, and 95% with SARS-CoV-1. 78% had Abs against SARS-CoV-2 nucleocapsid protein (NCP). However, 29% of patients had no immune response against the four spike protein epitopes. These participants also reported fewer symptoms, including no cases of anosmia/ageusia, suggesting mild illness. Anosmia/ageusia, fever, and cough associated significantly with higher Ab titers (Figure 4). Conclusion: Broad immune responses to various SARS-CoV-2 and related antigens were found among a heterogeneous patient population. However, less than 3 months after symptom onset, protective Ab responses to SARS-CoV-2 spike proteins were not detected in nearly one-third of recovered patients, primarily with mild infection. Intact sense of smell and taste demonstrated the greatest association with loss of seroprotective SARS-CoV-2 Ab responses, which may be clinically useful to predict post-infection immunity. Next steps include comparing the magnitude of Ab responses following full series completion with mRNA vaccination among this cohort. Disclosures: Robert Bencshop, PhD, Eli Lilly (Employee) Josh Poorbaugh, PhD, Eli Lilly (Employee) Ajay Nirula, MD/PhD, Eli Lilly (Employee, Shareholder) Lin Zhang, PhD, Eli Lilly and Company (Employee, Shareholder) Stephanie Beasley, BA, Eli Lilly (Employee)